2013
DOI: 10.1002/jbmr.2092
|View full text |Cite
|
Sign up to set email alerts
|

Single- and Multiple-Dose Randomized Studies of Blosozumab, a Monoclonal Antibody Against Sclerostin, in Healthy Postmenopausal Women

Abstract: Two clinical studies were conducted to assess the safety, tolerability, pharmacokinetics (PK), and pharmacodynamics (PD) of single and multiple doses (intravenous [iv] and subcutaneous [sc]) of blosozumab in postmenopausal women, including prior/current bisphosphonate (BP) users. In these phase 1, randomized, subject-and investigator-blind, placebo-controlled studies, subjects received escalating doses of blosozumab: single iv doses up to 750 mg, single sc doses of 150 mg, multiple iv doses up to 750 mg every… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
114
0
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 161 publications
(125 citation statements)
references
References 10 publications
8
114
0
2
Order By: Relevance
“…The similarity in this kinetics could reflect levels of sclerostin predominantly bound to blosozumab. BTMs in the subset of patients with previous bisphosphonate exposure showed similar dose-dependent responses, although with a lower magnitude (56).…”
Section: Sclerostin Antibodiesmentioning
confidence: 76%
See 1 more Smart Citation
“…The similarity in this kinetics could reflect levels of sclerostin predominantly bound to blosozumab. BTMs in the subset of patients with previous bisphosphonate exposure showed similar dose-dependent responses, although with a lower magnitude (56).…”
Section: Sclerostin Antibodiesmentioning
confidence: 76%
“…Another cohort received either blosozumab 150 mg or placebo SC. The other two cohorts with prior exposure to bisphosphonate received either 225 mg or 750 mg of IV blosozumab (56). The second phase I trial was a multiple-dose, multicenter, randomized, subject-and investigator blinded, placebo-controlled, parallel design study, in which 59 patients were randomized to either placebo or blosozumab SC (270 mg) or IV (750 mg) once every 2 weeks (Q2W), or blosozumab SC (180 or 270 mg) or IV 540 mg once every 4 weeks (Q4W ) for 8 weeks.…”
Section: Sclerostin Antibodiesmentioning
confidence: 99%
“…Overall, romosozumab increased bone formation and decreased bone resorption consistent with the results of the phase 1 studies with this sclerostin inhibitor and with blosozumab. 5,6 The pattern of response was, however, intriguing, showing an early rapid increase in bone formation markers followed by a progressive decline with time (Figure 1), which was not due to the development of …”
mentioning
confidence: 99%
“…4 Furthermore, in phase 1 human studies, increases in bone formation and decreases of bone resorption associated with significant increases in BMD were reported after administration of single doses of two different humanized antibodies, romosozumab (Amgen (Thousand Oaks, CA, USA), UCB (Brussels, Belgium)) and blosozumab (Eli Lilly, Indianapolis, IN, USA). 5,6 McClung et al 7 recently reported the results of a phase 2 clinical trial on the efficacy and tolerability of romosozumab in 419 postmenopausal women with low bone mass. This was a typical phase 2 study that compared different doses and dosing intervals of subcutaneous injections of romosozumab with placebo, oral alendronate, 70 mg weekly, and subcutaneous teriparatide, 20 mg daily.…”
mentioning
confidence: 99%
See 1 more Smart Citation